2023
DOI: 10.1001/jamanetworkopen.2023.13667
|View full text |Cite
|
Sign up to set email alerts
|

Association of 5α-Reductase Inhibitor Prescription With Bladder Cancer Progression in Males in South Korea

Abstract: ImportanceThe antiandrogenic effect of the 5α-reductase inhibitor (5-ARI) has been investigated for its role in preventing male-predominant cancers. Although 5-ARI has been widely associated with prostate cancer, its association with urothelial bladder cancer (BC), another cancer experienced predominantly by males, has been less explored.ObjectiveTo assess the association between 5-ARI prescription prior to BC diagnosis and reduced risk of BC progression.Design, Setting, and ParticipantsThis cohort study analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…The biological characteristics of the tumor, including the stage and grade of BC, were not adjusted between groups in this study because of the lack of information from the currently available NHISS dataset. However, in that approximately 40% of subjects took a 5ARI, this study is similar to the prevention results of recently reported 1:1 matched studies, which showed a reduction in BC diagnoses in 93,197 [ 8 ] and 5,300 [ 18 ] men who initiated 5ARI treatment compared to men who did not start a 5ARI. Second, we did not investigate the clinical outcomes between different formulations of 5ARIs, including finasteride and dutasteride, currently available on the market.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The biological characteristics of the tumor, including the stage and grade of BC, were not adjusted between groups in this study because of the lack of information from the currently available NHISS dataset. However, in that approximately 40% of subjects took a 5ARI, this study is similar to the prevention results of recently reported 1:1 matched studies, which showed a reduction in BC diagnoses in 93,197 [ 8 ] and 5,300 [ 18 ] men who initiated 5ARI treatment compared to men who did not start a 5ARI. Second, we did not investigate the clinical outcomes between different formulations of 5ARIs, including finasteride and dutasteride, currently available on the market.…”
Section: Discussionsupporting
confidence: 89%
“…While there was no significant difference in BC diagnosis within two years of 5ARI use (HR=1.05, 95% CI=0.82–1.32), the risk of BC diagnosis was significantly lower in the 5ARI group after 2 or more years of 5ARI use (HR=0.82, 95% CI=0.79–0.94) [ 10 ]. An et al [ 18 ] recently reported the outcome of a 1:1 propensity-matched study utilizing the nationwide cohort comparing 5,300 men diagnosed with BC. Compared with the control group, the 5ARI group had a lower risk of mortality (HR=0.83, 95% CI=0.75–0.91), bladder instillation (HR=0.84, 95% CI=0.77–0.92), and RC (HR=0.74, 95% CI=0.62–0.88).…”
Section: Discussionmentioning
confidence: 99%